A method to assess genomic DNA methylation using high-performance liquid chromatography/electrospray ionization mass spectrometry - Friso, Simonetta; Choi, Sang-Woon; Dolnikowski, Gregory G; Selhub, Jacob (Analytical chemistry (Washington), 2002)
Eukaryotic DNA is methylated at some cytosine residues, and this epigenetic feature performs critical functions. We developed a method for quantitative determination of 5-methyl-2'-deoxycytidine in human DNA using liquid chromatography/electrospray ionization mass spectrometry (LC/ESI-MS). The DNA was enzymatically hydrolyzed by sequential digestion with three enzymes. DNA hydrolyzates were subsequently separated by reversed-phase high-performance liquid chromatography in isocratic mode. The four major DNA bases and 5-methyl-2'-deoxycytidine were resolved and eluted in 13 min. Identification of 2'-deoxycytidine and 5-methyl-2'-deoxycytidine was obtained by combined diode array UV spectra analysis and mass spectra of chromatographic peaks. The isotopomers [15N3]-2'-deoxycytidine and (methyl-d3,ring-6-d1)-5-methyl-2'-deoxycytidine were used as internal standards. Ions of m/z 126 and 130 were used to detect 5-methyl-2'-deoxycytidine and its isotopomer, and ions of m/z 112 and 115 were used to detect 2'-deoxycytidine and its stable isotopomer, respectively. The DNA methylation status was calculated on the basis of the amount of 5-methyl-2'-deoxycytidine per microgram of DNA with percent relative standard deviations (%RSD) for a method precision of 7.1 (within-day) and 5.7 (day-to-day). This method also allows the measurement of 5-methyl-2'-deoxycytidine expressed as a percentage of total deoxycytidine residues in genomic DNA with %RSD for method precision of 1.9 (within-day) and 1.7 (day-to-day). This LC/MS method for quantitative determination of genomic DNA methylation status is rapid, sensitive, selective, and precise.